The study of mechanical properties of pineapple leaf fibre reinforced tapioca based bioplastic resin composite - Mathivanan, Davindrabrabu; Norfazilah, H.; Siregar, Januar Parlaungan; Rejab, M.R.M.; Bachtiar, Dandi; Cionita, Tezara (2016)
Natural fibre reinforced composite has brought the material engineering to a high new level of research. Natural fibres are compatible with matrices like polypropylene and can be used as reinforcement material to reduce the composition of plastic in a material. Natural fibres such as kenaf, pineapple leaf, and coir already found its importance in reducing the dependence of petroleum based products. However the biodegradability of the product at the end of the intended lifespan is still questionable. This has led many researches to look for a suitable replacement for synthetic fibres and achieve better adhesion between fibre and matrix. In this study, fiber and matrix which are hydrophilic in nature was used and the mixture was extruded and hot compressed to acquire better mechanical properties. The specimens were fabricated and tested according to ASTM D638. The 30% composition illustrates the best average modulus value among other composition and from this result it can be concluded that the increase of PALF fibre in TBR composite increases the modulus strength of the composite.